THE ROLE OF BUDDHIST MONKS IN RAISING DEMOCRATIC AWARENESS AMONG THAI YOUTH: A CASE STUDY OF THE SANGHA REGION 8 - ., PhraKhru Phisutthidhammaphon; Sangsachawat, Artit; Anoojarn, Sukkaput; Promjak, Weeranuch (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Study the current role of Buddhist monks in Ecclesiastical Region 8 in cultivating democratic consciousness among Thai youth, 2) Synthesize the roles of monks in promoting democratic values, and 3) Propose a model to enhance youth awareness of democratic governance by utilizing the roles of monks in the region. This was a qualitative study employing in-depth interviews with eight senior monks, small group discussions with 42 participants comprising Dhamma teachers, schoolteachers, and students, and model validation by five experts. The findings revealed that: 1) Monks in Ecclesiastical Region 8 play a significant role in fostering democratic awareness by integrating Buddhist teachings with democratic principles. They employ modern technology, media, and organize training programs that emphasize moral living through the integration of Dhamma and democratic values. 2) Content synthesis indicated that the monks’ roles align with democratic governance principles. They uphold the Vinaya (monastic discipline) as the highest code, respect the law, and operate within both spiritual and civic responsibilities. 3) The proposed model for promoting democratic consciousness among youth is consistent with the research objectives. It links democratic governance with Buddhist principles, is systematically structured, feasible in practice, measurable in outcome, and demonstrates efficiency. The model was confirmed by experts to be theoretically sound, applicable, and beneficial in terms of social, ethical, and educational value.